Using Bioluminescence Assay to Detect Snps Cause Drug Resistant of Mycobacterium Tuberculosis in Iraq - Hassan Kadhim Nemir1 , Ismail Aziz1 , Alaa Kareem Mohammed2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this search, a new bioluminescent technique was proved for pyrophosphate which was employed to single- nucleotide polymorphism (SNP) diagnosis using one-base extension reaction. Four Mycobacterium tuberculosis genes were chosen (Rpob, InhA, KatG, GyrA) genes. Fifty-four specimens were used in this study fifty-three proved as drug-resistant specimens by The Iraqi Institute of Chest and Respiratory Diseases in Baghdad., also one specimen was used as a negative control. The procedure of this assay was as follows. A specific primer within each aliquot owning a short 3-OH end of the base of the target gene was hybridized to the single-stranded DNA template. Then, (exo-) Klenow DNA polymerase and one of either ?-thio-dATP, dTTP, dGTP, or dCTP were supplemented and incubated for 1 min. Pyrophosphate freed by DNA polymerase is altered to ATP by pyruvate phosphate dikinase (PPDK), and the amount of ATP is measured using the firefly luciferase reaction. This technique, which does not demand expensive equipment, can be applied to rapidly monitor one-point mutation in the gene that causes drug resistant in mycobacterium tuberculosis. The results showed a high variation in values of ATP formation through matching and mismatch bases added. So, this assay (which required only five minutes), enable to find the gene SNP causes resistant for the specific drug